Sequential motion rates in the dysarthria of multiple sclerosis: A temporal analysis - Konstantopoulos, Kostas; Charalambous, Marina; Verhoeven, Jo (My University, 2011)
Dysarthria is present in 23 - 51% of multiple sclerosis (MS) patients, and the perceived characteristics of dysarthria have been shown to predict quality of life in these individuals. Tests of maximum performance such as oral diadochokinesis and Sequential Motion Rates (SMRs) are used in many neurology clinics and are considered to be sensitive indices of dysarthria. This large scale study investigated the SMRs in two groups of participants, i.e. MS dysarthrics and pair matched controls. The main conclusion of this study is that speech rate was significantly lower in the MS dysarthrics. This was primarily caused by longer stop gap durations and to a lesser extent the duration of the word-final vowels. The significance of measuring SMR rate to the description of dysarthria in the MS participants in this study holds promise for being a marker of disease progression and may have implications for speech therapy in these patients.
Keywords: Multiple sclerosis; Dysarthria; Sequential motion rate